UANG TUTUP BABAH SEBAGAI PENYELESAIAN PERKARA DALAM MASYARAKAT GAYO - Nurlaila, Mohd. Din, Taqwaddin. (Jurnal Ilmu Hukum, 2013)
Abstract: Article 98 verse (1) of the Act Number 11, 2006 regarding Aceh Governance states that customary law has a function and a role as a media for participation in society in conducting Aceh Governance in the province level and in the level of municipalities and districts in terms of security, peace, tolerance and law awareness in society. Verse (2) of the article also states that the settlement of social problems can be solved by customary approach through customary institutions. There are four types of crimes in Gayonese custom namely;Maas, Rujok, Died andBela. In fact, there are many a settlement of dispute in the society done through uangtutupbabah or hush money. The main problems of this research are (1) how is the process of giving this kind of money? (2) How is the strength of the decision of uangtutupbabah in solving the customary cases? (3) How is the impact of the decision in settling the case through this process on the society? This research aims to know the procedure of conducting the process, the strength of the decision in settling the case and the impact of the decision of settlement by the process of providing some money on the society. This is descriptive analytical research which is describing or depicting the implementation of the regulation in the context of legal theories and the implementation in the society and the effort of describing the explanation detailed, comprehensively and systematic of legal aspects in customary law. This is empirical legal research that is applying the existing norms if it is seen from the fact side. The sources of data are gathered from primary and secondary data. The research shows that firstly, the procedure or the stages of the implementation of providing money for shutting the mouth up in settling the cases in the community is that started from the report regarding a case to the third party (the party can be one of the village leaders or relatives that can be trusted), then the third party calls the reported person and ask the questions about the case followed by looking for the agreement of solving the case, one of the ways is by providing the money. Secondly, the decision of the process of the settlement by providing some money is obeyed by the people when the case occurs then providing the money solves it and the community follows it as it is inherited from their ancestors in the replacement of village leaders. Thirdly, the money might have painful effect on the perpetrator and other people due to the fact that it can be a shame; however the level of painful effect is different for every perpetrator. Every offense occurred is reported to the parents or the family of the criminals and it is necessary it is also reported to Reje Kampung or the king of the village where the villain live hence it might be having social sanction. It is recommended that Sarak Opat as a customary institution and village governance institution may complete facilities or the need of governance and the keeping of the documents, and in the implementation of the court procedure of customary Sarak Opat should be showing the ability and its honor before the society hence they will feel protected to report their problems. Key words:Customary Court and Hush Money (Uang Tutup Babah)